PEMANFAATAN LAHAN SEMPIT UNTUK BUDIDAYA SAYURAN DENGAN SISTEM VERTIKULTUR - Nurul Hidayati; Pienyani Rosawanti; Fahruddin Arfianto; Nanang Hanafi (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
The yard around as the most direct way of providing daily food and a source of income for the purchase of other foods. The yard around can provide enough nutritious food and income for the sale of yard around produce. However, the narrow yard is one problem to grow vegetables. Verticulture is a system of agricultural cultivation where the planting area arranged vertically or terraced to allow the efficiency of limited land. One solution for the community can develop a farm for providing food to families with the verticulture system. Vertikultur is a method of cultivation that the principle is the effective use of land. The benefit obtained is able to provide the family needed on vegetables and also make the atmosphere around the house to be fresher. Aesthetically, vertically landscaped gardens serve as a backdrop that presents beautiful scenery in various colors. This program was conducted at Perum PU Bukit Tunggal, Jekan Raya, Palangkaraya. Methods of this program by socialization with training and pamphlets and vegetables cultivation workshop verticulture and housewife as the participant. The purpose of this program can supply households with nearly all the foods they need, reducing the cost of vegetable spending for their family. Given the price of vegetables in the city of Palangka Raya quite expensive. The result of this program that is a housewife and their family can improving capability and skill on verticulture technology mastery like preparation of planting media, planting and plant treatment, pest and disease control, harvesting and post-harvesting treatment.